Creation in Dance - Fonseca de Almeida, Renata Mara (2023)
This study starts on the discussion about different ways of seeing. To remove the sense of sight out of the daily function to an aesthetic perception of reality, it presents contributions of authors as Merleau-Ponty (1992), Godard (2004), and Blanchot (2001). In a dialectic relation between see and create, it transforms distinct ways of seeing in an impulse to dance creation. The sight, considered through an esthetical and philosophical perspective, independently if it is a blind person or not, puts the creativity on movement. In this way, some experiments based on the relation between see and move, proposed by the author, are described along the text. The conclusion is that the way of seeing, that is to say, someone’s position in relation to the world, is what allows the creation, and not the physiological condition of sight’s sense.